A Comprehensive Review of Herbal and Synthetic Therapeutics in Managing Viral Diseases in Fish Health - Hasani, SJ; Nofouzi, K; Meshkiniy, S; Enferadi, A; Jalilzadeh, N; Ravvaz, A (Journal of the Hellenic Veterinary Medical Society, 2025)
Disease outbreaks are the main cause of financial loss in aquaculture, resulting in an estimated annual loss of over $10 billion. Fish viral diseases pose a continuous risk to the production of aquaculture, and despite advancements in the industry, approximately 10% of cultured aquatic animals succumb to infectious diseases, resulting in significant losses. Preventing and treating viral diseases in animals and humans is one of the most difficult tasks due to the varying effectiveness of vaccines, interferons, and other medications. While salmonids have been successful in controlling significant bacterial diseases through the use of antibiotics and vaccines, vaccines for viral diseases often prove to be ineffective. Standard antibiotics are not effective in preventing or treating viral diseases in fish. The risk of infectious disease outbreaks, including viral infections, increases with monoculture, as in the case of terrestrial agriculture. Unfortunately, the treatment of viral diseases often fails, highlighting the need for more research to find effective drugs and vaccines to manage viral diseases. This article explores the potential of using herbal and synthetic drugs to combat viral diseases that impact fish populations.